Introduction - Wujastyk, Dagmar; Newcombe, Suzanne; Barois, Christèle (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
Wild and diverse outcomes are associated with transmutational practices: the prolongation of life, the recovery of youth, the cure of diseases, invincibility, immortality, enlightenment, liberation from the cycle of rebirths, and unending bliss. This range of outcomes is linked to specific practices taught in separate traditions and lineages in medical, alchemical, yogic and tantric milieus across South and Inner Asia. These practices can be individual or collective, esoteric or secular, and occur in different places from hospital to village to monastery; they involve transmutations of substances as well as transmutations of the body. Every expression by a particular lineage has a distinguishing articulation. Yet there are also very clear commonalities and interconnections between the traditions’ aims, methods and expected results. In this special issue of HSSA, we examine transmutational practices and their underlying concepts in this wider context of South and Inner Asian culture. How do these practices and ideas connect and cross-fertilise? And conversely, how are they delineated and distinct?